THE CORRELATION BETWEEN STUDENTS’ INTEREST AND THEIR READING COMPREHENSION LEVEL IN SHORT PASSAGES - Jihan Alfaizah; Wahyuddin Naro; Kamsinah Kamsinah (Universitas islam Negeri Alauddin Makassar, 2020)
The study aims at finding out the relationship between students’ interest and their reading comprehension level in short passages. This study was conducted at the second grade of Senior High School 10 of Gowa. The population of this study was all of the students in academic year 2019/2020 which consisted 265 students, and the sample was 30 students selected by using purposive method. The researcher applied correlational design. The researcher used the instrument to obtain the data, they were questionnaire and test. The scores from both instruments were calculated and analyzed by using statistical procedure of Product Moment Correlation to find out whether there was a correlation between the two variables or not. The result showed that there was low correlation with the index value of correlation coefficient (rxy) of 0.28. Furthermore, the hypothesis testing showed that the index value of correlation coefficient (rxy) of 0,28 was lower than the index value of correlation coefficient of the Product Moment table (rt) of 0,306 which meant that, the null hypothesis (H0) was accepted and alternative hypothesis (H1) was rejected. Therefore, students’ interest in short reading comprehension passages is in average level because only a few students are interested in English lesson especially those who have high interest and many vocabularies to learn English. Short Passages did not give a big impact on students’ interest and their achievement in reading comprehension because of some factors. There is not self-interest in reading, lack of vocabulary and support parents and all of school elements in order to improve the students’ reading interest optimally. The findings of this study might be used as the input for both teachers and students to improve students’ reading comprehension level.